Moderating effect of the digital divide of e-commerce (2019)
Purpose: The purpose of this paper is to examine whether the digital divide has a moderating effect on the technological factors that affect the adoption of electronic commerce. Design/methodology/approach: This study proposes an exploratory empirical model that integrates the basic variables of e-commerce adoption through the use of the technology adoption model, making an extension with the facilitating conditions and the digital divide as a moderating variable. A digital survey was randomly distributed in Colombia, reaching a final sample of 745 electronic buyers. Findings: The explanatory result validates that the perception of the digital divide negatively moderates the influence of the variables related to internet technology on the use of e-commerce. Originality/value: This one of the first studies that analyzes the effect of the digital divide on the adoption of e-commerce. © 2019, Emerald Publishing Limited.